Adapting Literature Circles for Critical Thinking in Indonesian EFL Classrooms: A Qualitative Case Study Aligned with SDG 4 - Junie Darmaningrum; Lies Amin Lestari; Pratiwi Retnaningdyah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To investigate how Literature Circles can be pedagogically adapted to the Indonesian English as a Foreign Language (EFL) context to foster students' critical thinking while accommodating curriculum requirements, students' language proficiency, and classroom learning needs in support of Sustainable Development Goal (SDG) 4. Method: A qualitative case study was conducted at an Indonesian senior high school involving one English teacher and twelve eleventh-grade EFL students. Data were collected through classroom observations, semi-structured interviews, and document analysis, including lesson plans, students' worksheets, dialogue journals, and learning products. The data were analyzed using coding, categorization, thematic analysis, and triangulation. Results: The findings revealed that Literature Circles were successfully adapted through modifications to instructional procedures, collaborative learning stages, reading materials, and role assignments, including the addition of Text Analyzer and Grammar Pointer roles to align with the Indonesian genre-based curriculum. These adaptations promoted six dimensions of critical thinking interpretation, analysis, inference, evaluation, explanation, and self-regulation while enhancing students' affective, cognitive, and behavioral engagement in collaborative learning. Novelty: The study proposes a contextualized adaptation model of Literature Circles for Indonesian secondary EFL classrooms, demonstrating how collaborative reading can be integrated with curriculum demands to foster critical thinking, student engagement, and the achievement of Sustainable Development Goal 4 (SDG 4) through student-centered learning.